A Double-Flipped Virtual Classroom Format for Medical Students Learning Ophthalmology: An Approach to Clinical Rotations in the Context of COVID-19 - Brady, S. Taylor; Vegunta, Srav; Olson, Lenora M.; Brintz, Ben J.; Pettey, Jeff H.; Jardine, Griffin J. (Journal of Academic Ophthalmology, 2022)
Purpose The aim of this study was to assess efficacy of a virtual, double-flipped clinical rotation in ophthalmology for medical students during the coronavirus disease 2019 (COVID-19) pandemic.Methods We instituted a virtual, reverse-classroom clinical elective for eight medical students interested in ophthalmology as a career. The course included required prework, interactive case-based discussions, and follow-up quizzes (first flip) entirely prepared and delivered by the students as teachers (second flip). After completion of the course, we surveyed students on five domains: (1) Autonomy and Leadership, (2) Self-Efficacy, (3) Impact on Career Selection, (4) Quality of Educational Experience, and (5) Clear Goals and Feedback using a Likert scale of 1–5 (5 being the most positive). We also asked open-ended questions regarding the overall experience, that is, strengths, weaknesses, and future recommendations for the course. Due to the small N and exploratory nature of the study, no formal statistical inference was performed.Results Seven students responded to the survey. Aggregated mean survey scores for each domain are represented in parentheses. Responses were very positive in regard to “Autonomy and Leadership” (4.5), “Impact on Career Selection” (4.1), “Quality of Educational Experience” (5.0), and “Clear Goals and Feedback” (4.4). “Self-Efficacy,” which had an emphasis on ability to perform an eye exam and basic knowledge of ophthalmology, had a lower mean (3.4). The subjective responses were also very positive, but similarly alluded to the limitation of learning examination skills virtually.Conclusions A medical school clinical elective can be successfully executed in a virtual format with an emphasis on student-directed learning. The novel “double-flipped” approach was highly rated by our small sample size. However, there remained a glaring limitation in the ability to transfer clinical skills in the virtual format. In the context of limited in-person contact due to the COVID-19 pandemic, we believe that the double-flipped, virtual format was a viable replacement for a traditional clinical rotation.
Keywords: medical education; flipped classroom; ophthalmology; COVID-19 pandemic education; medical students; residents; virtual learning; online learning; clinical rotation